John Steinbeck - Lennart Edling:::Creator::::::::::::
John Steinbeck talking with the Swedish Prime Minister Tage Erlander, and his wife Aina Erlander, a Swedish lecturer, at the Nobel Prize ceremony. Original is in the safe.